8 A CASE OF DIABETIC MUSCLE INFARCTION: A RARE COMPLICATION OF DIABETES MELLITUS. (10th December 2015) - Ashley, K. E.; Frost, J.; Sanders, S.; Kirchner, K.; Montgomery, Sonny G.V.
Abstract : Diabetic muscle infarction (DMI) was first described in 1965 but since that time, there has been a paucity of cases reported in the literature. A 56-year-old African-American man with type 2 DM of more than 5 years' duration, diabetic neuropathy, hypertension, and dilated cardiomyopathy presented to the VA Medical Center in Jackson, MS, with complaints of acute onset of left thigh pain and swelling of approximately 2 weeks' duration. He denied history of trauma or recent infection. He denied fever, chills, night sweats, rashes, paresthesias, or weakness in his extremities. The severity of the pain precluded him from putting weight on his left leg. On examination, he was afebrile with normal vital signs. He had clinical evidence of CHF. Upon examination of his lower extremities, he was noted to have only trace edema around his ankles but 2+ pitting edema of his left posteromedial thigh. This was very tender to palpation but was not erythematous or warm. There were no skin lesions or rashes. Dorsalis pedis pulses were palpable and equal bilaterally and there was no joint involvement. His muscle strength was not fully tested because of the extreme pain in his leg. Laboratory examination was normal except an elevated glucose, a low albumin level, and elevated alkaline phosphatase. His CPK was normal. His erythrocyte sedimentation rate was elevated and the hemoglobin A1c was 11.8. MRI of the leg showed intense enhancement of the muscles of the left thigh with increase in size and extensive subcutaneous edema. Muscle biopsy showed myopathic changes secondary to diabetic vascular disease with massive scarring and a few peripheral fascicles of ischemic muscle fibers, making the diagnosis of diabetic muscle infarction. DMI is a rare condition that usually affects patients with long-standing or poorly controlled DM. Affected patients typically present with the acute onset of painful swelling of the thigh or calf that then evolves over days to weeks. Muscle enzyme levels may be normal or increased, depending on the stage of the infarction at presentation. Elevated erythrocyte sedimentation rates as well as leukocytosis may also occur. For the most part, laboratory studies should be used to exclude other potential diagnoses.